2014
DOI: 10.1002/anie.201310374
|View full text |Cite
|
Sign up to set email alerts
|

An Antiaromatic Electrode‐Active Material Enabling High Capacity and Stable Performance of Rechargeable Batteries

Abstract: Although aromatic compounds occupy a central position in organic chemistry, antiaromatic compounds have demonstrated little practical utility. Herein we report the application of an antiaromatic compound as an electrode-active material in rechargeable batteries. The performance of dimesityl-substituted norcorrole nickel(II) complex (NiNC) as a cathode-active material was examined with a Li metal anode. A maximum discharge capacity of about 207 mAhg(-1) was maintained after 100 charge/discharge cycles. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
119
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(122 citation statements)
references
References 27 publications
3
119
0
Order By: Relevance
“…The first electrochemical reduction, attributable to a reaction from Ni(nor) to Ni(nor) ·− (ref. 21), appeared at −0.65 V versus Ag/AgCl (Supplementary Note 10). Subsequent electrochemical single-molecule conductance experiments brought the LUMO-mediated transport channel closer to the electrode potential as the electrochemical potential was changed from +0.45 to −0.30 V versus Ag/AgCl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first electrochemical reduction, attributable to a reaction from Ni(nor) to Ni(nor) ·− (ref. 21), appeared at −0.65 V versus Ag/AgCl (Supplementary Note 10). Subsequent electrochemical single-molecule conductance experiments brought the LUMO-mediated transport channel closer to the electrode potential as the electrochemical potential was changed from +0.45 to −0.30 V versus Ag/AgCl.…”
Section: Resultsmentioning
confidence: 99%
“…1). Ni(nor) features a chemically stable, structurally rigid antiaromatic porphyrinoid moiety202122 where antiaromaticity can be preserved due in no small part to its molecular rigidity. The electronic properties of Ni(nor) are benchmarked against a porphyrin-based aromatic counterpart, Ni(porph) (Fig.…”
mentioning
confidence: 99%
“…Among the tetrapyrrolic systems (Scheme ), that is, porphyrins (Por) and corroles (Corr), the delocalization results in the aromatic character of the macrocycle, which is in line with the 4 n +2 Hückel rule and the presence of eighteen π electrons in the macrocyclic conjugation circuit. In norcorrole (NCR), a recently discovered tetrapyrrole, the conjugation path involves sixteen π electrons, and thus, the system becomes antiaromatic . To some extent, the reactivity of the macrocycle and some other properties, for example, the redox behavior of norcorrole in its nickel(II) complex (NCRNi, 1 ) resemble those of aromatic systems.…”
Section: Introductionmentioning
confidence: 99%
“…NiNC displays to be antiaromatic because of its highly planar structure and the presence of 16 π electrons along the conjugation circuit. Only Shin et al reported the practical application of the antiaromatic NiNC as an electrode-active material in a Li metal free rechargeable battery [15]. It showed that NiNC had the bipolar redox property [14,15].…”
Section: Introductionmentioning
confidence: 98%